A communication interface module for PC to ISDN; Interfacing a high speed processor PC to ISDN; Incorporating ISDN protocol handler concepts in integrated voice and data; Interfacing graphic data to ISDN; A facsimile communication interface module to ISDN / [mikrofilem] - 242322 Chieng, Lay Min; Chieng, Lay Min; Soh, Wah Hon; Uthaya Kumar Swaminatha Pillai; Yeap, Lai Chong; Yeong, Jiun How (Sekudai : UTM, 1995)
Project paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1995